Cytotoxic Activity of Bioactve Compounds from Hydroid Aglophenia cupressina Lamoureoux against Hela Tumor Cells - Sjafaraenan, Sjafaraenan; Johannes, Eva; Herwin, Herwin (International Journal of Applied Biology, 2024)
Hydroids are marine invertebrates living on sponges, which belong to the phylum Coelenterata. They also contain several chemical compounds, including alkaloids, steroids, terpenoids, and histamine, which can be used as medicinal raw materials, such as antimicrobials and anticancer. Therefore, this study aimed to assess the working mechanism of active compounds obtained from the extract and the fraction of Hydroid Aglaophenia cupressina Lamoureoux against Hela ttumor cell line, as a solvent used n-hexane.  The cytotoxic activity was carried out by using MTT method.  The results showed both extract and fraction activities against Hela tumor cells. They were also categorized as moderate cytotoxic activity based on the IC50 values of the extract and fraction, namely 0.31726 µg/mL and 0.32712 µg/mL, respectively.